Media Pembelajaran Shalat Menggunakan Augmented Reality (Studi Kasus SD Negeri 1 Bumijawa) - Aji Maemun Syukron; Rony Wijanarko (Universitas Wahid Hasyim, 2025)
Prayer is the main act of worship in Islam after the shahada. The procedures for carrying out this act of worship must be orderly and in accordance with the procedures that have been determined. Most learning currently still uses books so it is less effective and informative. Learning can run effectively if all influential components support each other to achieve learning goals. To facilitate learning activities, especially in Prayer Learning, teachers should prepare teaching materials to help make it easier for students to understand the learning material. Therefore, appropriate learning media is needed, one of which is Augmented Reality-based media. The application was created using Unity and Blender and used the Black box testing method by testing the application, lighting and paper type. This application is intended to make students more interested in teaching and learning activities and makes it easier for students to learn so that maximum results are achieved.